Electrophysiological effects of tamoxifen: mechanism of protection against reperfusion arrhythmias in isolated rat hearts - Diez, Emiliano Raúl (2013)
Reperfusion arrhythmias are currently attributed to ionic imbalance and oxidative stress. Tamoxifen is a potent antioxidant that also modulates some ionic transport pathways. In this work, we tried to correlate the electrophysiological effects of 1, 2, and 5 μM of tamoxifen with the incidence and severity of arrhythmias appearing on reperfusion after 10 minutes of coronary occlusion in isolated hearts from female rats. All tamoxifen concentrations inhibited the action potential shortening observed in the control hearts during late ischemia (6-10 minutes), whereas 2 and 5 μM also reduced the resting membrane potential depolarization. The incidence of sustained ventricular tachycardia and/or ventricular fibrillation on reperfusion decreased from 10 of 12 (control group) to 5 of 10 (1 μM, P = 0.1718), 4 of 12 (2 μM, P = 0.0361), and 2 of 10 (5 μM, P = 0.0083). The possible role of chloride currents activated by cell swelling in these effects was explored in hearts submitted to a 10-minute hypotonic challenge, where tamoxifen (5 μM) blocked the action potential shortening and the late resting membrane potential depolarization produced by hypotonicity, mimicking its action in late ischemia. Tamoxifen produced a similar increase of the total antioxidant capacity of myocardial samples at all the concentration tested. In conclusion, our data strongly suggest that the antiarrhythmic action of this agent is mediated by its electrophysiological effect derived from modulation of chloride currents activated by cell swelling.